Journey of the Midnight Sun - Afzal, Shazia (Orca Book Publishers, 2022)
"A beautiful picture book based on the true story of the Midnight Sun Mosque that traveled 4,000 kilometers across Canada to become one of the most northern mosques in the Arctic Circle."--